If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -4) = 7(x + 3) Reorder the terms: 4(-4 + 2x) = 7(x + 3) (-4 * 4 + 2x * 4) = 7(x + 3) (-16 + 8x) = 7(x + 3) Reorder the terms: -16 + 8x = 7(3 + x) -16 + 8x = (3 * 7 + x * 7) -16 + 8x = (21 + 7x) Solving -16 + 8x = 21 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -16 + 8x + -7x = 21 + 7x + -7x Combine like terms: 8x + -7x = 1x -16 + 1x = 21 + 7x + -7x Combine like terms: 7x + -7x = 0 -16 + 1x = 21 + 0 -16 + 1x = 21 Add '16' to each side of the equation. -16 + 16 + 1x = 21 + 16 Combine like terms: -16 + 16 = 0 0 + 1x = 21 + 16 1x = 21 + 16 Combine like terms: 21 + 16 = 37 1x = 37 Divide each side by '1'. x = 37 Simplifying x = 37
| -(t-2)+4=-3 | | 11x-30=22x-16 | | x-6/5=12 | | 8d+2/3=4 | | 12x-7=5x-56 | | 6x+8x-36=90-4x | | 6=y-1 | | 12=x+18 | | 1.80+0.48=0.42+1.80 | | x^2-1/36 | | x^2+16-57=0 | | 8x-6x+168=8x+90 | | X^2+Y^2-16X+6Y+53=0 | | 6.42-10*d=2.5 | | 9x+18=9x+12 | | 25=n+20 | | -3(3-4m)-6m=39-2m | | 6-2x=6y-10x+10 | | 6-4y=6 | | -5c/820 | | 1/4*h+4=0.25 | | 6/5=10/7x+6 | | 3(c+1)+1=10 | | 3(5+2(11-x)-5)=5(x+6)-4x+5 | | 5=10-5x^2 | | 8x+12=9x-4 | | 6/5=15/8x+5 | | 1/3*a-6=-15 | | 2x+2=4x-12 | | 9+6t=6t+9 | | -5x^2+3x+9=0 | | 13b+-11b=-16 |